Penerapan rumah pengering ultraviolet untuk pengeringan tepung timphan di Gampong Ujong XII Aceh Besar (Ultraviolet drying chamber application for drying timphan flour in Ujong XII Village, Aceh Besar District - Ratna, Ratna; Aprilia, Sri; Bulan, Ramayanty; Devianti, Devianti (Universitas Syiah Kuala, 2021)
The implementation of this service aims to introduce an ultraviolet (UV) drying chamber, drying techniques/manufacture of pumpkin flour, and glutinous rice flour to reduce the dependence of women members in family welfare empowerment group (Pemberdayaan Kesejahteraan Keluarga/PKK) and women members in Integrated Service Post (Pos Pelayanan Terpadu/Posyandu) in Ujong XII Village on the use of flour in the market and replace it with processed flour. The approach method offered in this Product-Based Community Service activity is counseling and training on the manufacture of pumpkin flour and glutinous rice using a UV innovation greenhouse effect dryer. The results achieved in this service are the capacity of the drying house 30 kg with an average drying temperature of 55 C. The community has the skills and practice of processing and drying timphan flour in the form of pumpkin flour and glutinous rice flour. In conclusion, the application of a UV dryer house can facilitate the drying of raw materials for making timphan.